2017
DOI: 10.1017/s003329171700157x
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of visuospatial associative memory following a first psychotic episode: a long-term follow-up study

Abstract: Areas of cognition that develop prior to psychosis onset, such as visuospatial and verbal associative memory, may be preserved early in the illness. Later deterioration in visuospatial memory ability may relate to progressive structural and functional brain abnormalities that occurs following psychosis onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Although previous studies have also identified visuospatial associative memory deficits in individuals with chronic schizophrenia (Wood et al ., 2002; Stip et al ., 2005; Donohoe et al ., 2008), prior studies of recent-onset patients found preserved functioning in this domain (Wood et al ., 2002; Barnett et al ., 2005; Wannan et al ., 2018), with deterioration occurring only after illness onset (Haring et al ., 2017; Wannan et al ., 2018). One potential explanation for the visuospatial associative memory deficit in our recent-onset group is their longer duration of illness compared with previous studies (Wood et al ., 2002; Wannan et al ., 2018). Given that the most pronounced brain changes in schizophrenia-spectrum illness have been shown to occur in the first 6–12 months following illness onset (Bartholomeusz et al ., 2017), we might expect that cognitive decline would occur in a similarly short period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although previous studies have also identified visuospatial associative memory deficits in individuals with chronic schizophrenia (Wood et al ., 2002; Stip et al ., 2005; Donohoe et al ., 2008), prior studies of recent-onset patients found preserved functioning in this domain (Wood et al ., 2002; Barnett et al ., 2005; Wannan et al ., 2018), with deterioration occurring only after illness onset (Haring et al ., 2017; Wannan et al ., 2018). One potential explanation for the visuospatial associative memory deficit in our recent-onset group is their longer duration of illness compared with previous studies (Wood et al ., 2002; Wannan et al ., 2018). Given that the most pronounced brain changes in schizophrenia-spectrum illness have been shown to occur in the first 6–12 months following illness onset (Bartholomeusz et al ., 2017), we might expect that cognitive decline would occur in a similarly short period.…”
Section: Discussionmentioning
confidence: 99%
“…Visuospatial associative memory was measured using the Visuospatial Paired-Associate Learning (PAL) Task from the CANTAB (Cambridge Cognition, 2018). Details of this task have been described previously (Wannan et al ., 2018). The total number of trials required to locate all of the patterns correctly in all stages of the task was the variable of interest, and therefore lower scores are better.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A closer examination of this profile indicated that although all groups were comparable on overall visual learning performance, the neurodevelopmental cohort made more errors. This may reflect impaired processes specific to EP and ASD including impaired visual working memory (109,110) and slow processing speed (114,115). Attentional processes were the most salient features that discriminated the EP group from the combined ASD/SAD cohort and EP from the SAD groups.…”
Section: Discussionmentioning
confidence: 98%